2022
DOI: 10.3389/fmars.2022.932375
|View full text |Cite
|
Sign up to set email alerts
|

Remote reef cryptobenthic diversity: Integrating autonomous reef monitoring structures and in situ environmental parameters

Abstract: Coral reef sessile organisms inhabiting cryptic spaces and cavities of the reef matrix perform vital and varied functional roles but are often understudied in comparison to those on exposed surfaces. Here, we assess the composition of cryptobenthic taxa from three remote tropical reef sites (Central Indian Ocean) alongside a suite of in situ environmental parameters to determine if, or how, significant patterns of diversity are shaped by local abiotic factors. To achieve this, we carried out a point-count anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 95 publications
1
1
0
Order By: Relevance
“…In this study, the plate faces showed the strongest variation in sessile benthic composition, in agreement with previous studies that demonstrated the importance of the plate surface in the sessile benthic community composition [7]. For example, Steyaert et al [28] reported that the plate faces (top or bottom) had a significant impact on the percentage covers of various organisms, including bryozoans, gastropods, soft and calcified tube worms, CCA, and fleshy red, brown, and green encrusting macroalgae on ARMS. Our results show that the high occurrences of CCA and Rhodophyta on the top faces, coupled with the high occurrences of Bryozoa, Annelida, and Chordata on the bottom faces, distinctly illustrate a pattern that is likely influenced by light exposure.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, the plate faces showed the strongest variation in sessile benthic composition, in agreement with previous studies that demonstrated the importance of the plate surface in the sessile benthic community composition [7]. For example, Steyaert et al [28] reported that the plate faces (top or bottom) had a significant impact on the percentage covers of various organisms, including bryozoans, gastropods, soft and calcified tube worms, CCA, and fleshy red, brown, and green encrusting macroalgae on ARMS. Our results show that the high occurrences of CCA and Rhodophyta on the top faces, coupled with the high occurrences of Bryozoa, Annelida, and Chordata on the bottom faces, distinctly illustrate a pattern that is likely influenced by light exposure.…”
Section: Discussionsupporting
confidence: 93%
“…At each sampling site, water temperature was recorded and was between 29.3°C and 30°C during the whole sampling period. A previous study at a nearby site in the southwest of the lagoon described this area to have a low and stable flow velocity of ~0.2 m/s and wave height of ~0.25 H s (m) (Steyaert et al., 2022). Conditions during this study were likely to be similar, and there were no significant weather events during the sampling period.…”
Section: Methodsmentioning
confidence: 99%